Analisis Kerja Ergonomi dengan Metode REBA pada Pemasangan Spark Plug di PT XY - Tofa Luwih Apriandi; Supriyati Supriyati; Supriyanto Supriyanto (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study aims to evaluate the ergonomic risk level in the spark plug installation process at PT XY to identify musculoskeletal complaints and provide recommendations for improvement. The Nordic Body Map method was used to identify areas of the body experiencing complaints, while the Rapid Entire Body Assessment was used to evaluate the risk level of work posture. The results revealed that the most complaints were found in the wrists, neck, back, and arms. An initial REBA score of 13 indicated a very serious risk level, requiring immediate corrective action. Proposed improvements were made through changes to the work layout by bringing the rack closer and eliminating excessive bending activities. After improvements were made, the REBA score decreased to 3, which indicates a relatively low risk level. Thus, ergonomic improvements have been proven to increase comfort and reduce the potential for work injuries in spark plug installation operators.